Clinical and evidence-based considerations for choosing a pneumococcal conjugate vaccine in India: A narrative review - Vijay Yewale; Pallab Chatterjee; Sanjay M. Marathe; Santosh Taur; Sripriya Sathyanarayanan (Human Vaccines & Immunotherapeutics)
Immunization plays a crucial role in protecting children from life-threatening conditions such as pneumococcal disease. Pneumococcal disease can affect multiple organ systems and manifest as an invasive or noninvasive disease. Despite being preventable by vaccines, it remains a public health concern in India. The development of pneumococcal conjugate vaccines (PCVs) has helped reduce the burden of pneumococcal disease by overcoming the limitations of polysaccharide vaccines, especially in young children. Although immunogenicity is used as a proxy for the evaluation and approval of PCVs, results from immunogenicity studies have been bridged back to vaccine trial efficacy. Post-approval effectiveness and impact of new PCVs must be established. This review aims to consolidate evidence-based considerations that play a role in the evaluation of PCVs. Critical aspects related to the assessment of vaccines, their importance, and limitations in real-world contexts are discussed in this review.